2018
DOI: 10.25004/ijpsdr.2018.100507
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions Between Concomitantly Administered Phenytoin With Rivaroxaban

Abstract: In the present investigation it was aimed to evaluate any possible pharmacokinetic interactions between Phenytoin and Rivaroxaban. Study was conducted in Male Wistar rats; animals were divided into three groups. Group 1 received Phenytoin alone, Group 2 received Rivaroxaban alone and Group 3 received Phenytoin and Rivaroxaban concomitantly. The treatment was given for 8 days and the blood samples were collected on day 1 and day 8. The samples were analyzed by HPLC. The results were show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, there were no studies conducted to investigate the effects of CBZ or PHT (CBZ/PHT) on both the pharmacokinetics (PK) and the pharmacodynamics (PD) of RIV. Only one study was reported the effects of PHT on the PK of RIV; however, no information regarding administered doses was reported [31]. Our study was, therefore, conducted to solve the lack of information.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there were no studies conducted to investigate the effects of CBZ or PHT (CBZ/PHT) on both the pharmacokinetics (PK) and the pharmacodynamics (PD) of RIV. Only one study was reported the effects of PHT on the PK of RIV; however, no information regarding administered doses was reported [31]. Our study was, therefore, conducted to solve the lack of information.…”
Section: Introductionmentioning
confidence: 99%